Non-audit fees, institutional monitoring, and audit quality - Ding, David K. (2013)
We posit that the effect of non-audit fees on audit quality is conditional on the extent of institutional monitoring. We suggest that institutional investors have incentives and the ability to monitor financial reporting quality. Because of the reputation concerns and potential litigation exposure, auditors are likely to provide high audit quality, when they also provide non-audit services to clients, particularly when clients are subject to high institutional monitoring. We find evidence that, as non-audit fees increase, audit quality (measured by performance-adjusted discretionary current accruals and earnings-response coefficients) reduces only for clients with low institutional ownership but not for clients with high institutional ownership. Our results are robust after controlling for auditor industry specialization, firms’ operating volatility, size effect, and potential endogeneity between institutional ownership and audit quality.